Creativity Pattern of Problem Posing in Mathematics for Moderately Capable Students in Cross-Situations - Liani, Ahyani Mirah; Arsyad, Nurdin; Awi (International Journal of Education, Vocational and Social Science, 2026)
This study aims to describe the pattern of creativity in mathematical problem posing among students with moderate mathematical ability across different situations. Creativity is analyzed through three indicators: fluency, flexibility, and novelty. This qualitative descriptive study involved students of the Primary School Teacher Education Program (PGSD) at Universitas Negeri Makassar, selected using purposive sampling based on moderate mathematical ability test results. Data were collected through mathematical problem-posing tasks involving free, semi structured, and structured situations, supported by semi-structured interviews. The findings indicate that students with moderate mathematical ability demonstrate relatively consistent fluency across situations, as they are able to generate several relevant mathematical problems. However, flexibility and novelty are limited and fluctuate depending on the characteristics of the situation. Free and semi-structured situations provide more opportunities for idea variation, while structured situations tend to restrict creativity, resulting in routine and procedural problems. These results highlight the importance of designing adaptive problem posing situations to support the development of students’ mathematical creativity. These results suggest that instructional designs incorporating adaptive and balanced problem posing situations are essential to support the development of flexibility and novelty in students’ mathematical creativity.